Development and evaluation of The KIT: Keeping It Together™ for Youth (the 'Youth KIT') to assist youth with disabilities in managing information. (22nd October 2014) - Freeman, M.; Stewart, D.; Shimmell, L.; Missiuna, C.; Burke‐Gaffney, J.; Jaffer, S.; Law, M.
Abstract Background This article presents findings from the development and evaluation of The KIT: Keeping It Together™ for Youth (the 'Youth KIT'). The Youth KIT is a resource intended to assist youth with disabilities during their teenage years and during the transition to adulthood to give information to others about themselves, get from others about themselves, and organize their own information to the best of their ability. Methods Thirty‐six youth between the ages of 12 and 25 with physical and developmental disabilities were active participants in the development of the Youth KIT and partnered with a multidisciplinary team to conduct the qualitative evaluation. Focus groups and individual interviews were used in three phases of evaluation. Results The results of qualitative content analysis found the Youth KIT to be useful for a variety of youth in different contexts. The themes that emerged about the utility and impact of the Youth KIT were: (1) self‐discovery for youth; and (2) the importance of the 'fit' between youth and mentors to support youth as they started to use the Youth KIT. Conclusion Clinical implications for healthcare providers working with youth during the transition to adulthood include recognition that discussions about adult goals should be a continuous dialogue throughout adolescence rather than a 'special' conversation occurring at the time of discharge from paediatric services.